Questioning State Supervision in Guaranteeing Halal Products in Indonesia - Irsyadul Muttaqin; Dhia Al Uyun; Riana Susmayanti (Department of Sharia Economic Law, Faculty Sharia and Law, UIN Sunan Gunung Djati Bandung, 2025)
This article examines the state's responsibility in ensuring the halal status of products in Indonesia by highlighting the weaknesses in the implementation of the Halal Product Assurance Law. The formation of Government Regulation No. 42/2024 has created an illusory authority for the BPJPH and reinforced the fragmentation of authority between the BPJPH and related ministries in the supervision of halal products. As a result, legal uncertainty and the emergence of double standards have weakened BPJPH's role in supervisory implementation. This study uses a doctrinal legal analysis approach to halal product assurance legislation, focusing on text interpretation, identification of ambiguities, and disclosure of normative conflicts between the Halal Product Assurance Law, the Job Creation Law, and Government Regulation No. 42/2024. The analysis shows that institutional fragmentation in the supervision of the Halal Product Assurance has weakened BPJPH's authority. Instead of enforcing adequate supervision, the disharmonious institutional distribution design has created legal uncertainty, sectoral ego, and the risk of abuse of discretion, so that the substantive supervisory function has not been achieved and has legal implications for the state's failure to fulfill the objectives of Sharia law. A comparison with Malaysia shows that the centralization of authority under JAKIM, reinforced by criminal regulations, has resulted in a more integrated and consistent halal supervision system. This article emphasizes the need for institutional reform that affirms BPJPH's centralization as the sole authority and strengthens legal instruments by revising the Halal Product Assurance Law.